2022
DOI: 10.21203/rs.3.rs-1479424/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher versus lower dose corticosteroids for severe to critical COVID-19: A systematic review and dose-response meta-analysis

Abstract: Purpose Corticosteroids are standard of care for patients with severe COVID-19. However, the optimal dose is uncertain. We compare higher doses of corticosteroids with lower doses in patients with COVID-19. Methods We searched MEDLINE, Embase, Cochrane Central Register of Controlled Trials, MedRxiv, and Web of Science from inception to January 7, 2022, for trials that randomized patients with severe-to-critical COVID-19 to corticosteroids, standard care, or placebo. Reviewers, working in duplicate, screened … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This review only included seven out of the 17 RCTs in our review, which may explain the observed difference. 15 Of note, the results from our sensitivity analyses assessing all corticosteroids were similar to their findings, although we could not rule out an increase in mortality.…”
Section: Relation To Current Evidencesupporting
confidence: 58%
See 4 more Smart Citations
“…This review only included seven out of the 17 RCTs in our review, which may explain the observed difference. 15 Of note, the results from our sensitivity analyses assessing all corticosteroids were similar to their findings, although we could not rule out an increase in mortality.…”
Section: Relation To Current Evidencesupporting
confidence: 58%
“…Higher versus lower doses of corticosteroids in hospitalised adults with COVID-19 have also been compared in other systematic reviews and meta-analyses of observational studies and RCTs. [14][15][16][17] All used a higher cut-off for high-dose treatment (range 10-20 mg of dexamethasone) than in our review. [14][15][16][17] None assessed days alive without life support, which may be of importance during periods with high caseloads and strained ICU capacity.…”
Section: Relation To Current Evidencementioning
confidence: 99%
See 3 more Smart Citations